(untitled) (Bangladesh Medical Journal Khulna, 2014)
This study was done to evaluate the trend of liaison of different clinical department with Psychiatry considering their referral rate to the Psychiatry Unit of Khulna Medical College Hospital. The study was done over a twelve month period (Jan 2012 to December 2012). All the patients (672) referred by different departments were included. Among the patients, 72.9% was referred by Medicine & 8.9% by Pediatrics department. Major depressive disorder, Anxiety disorders and Schizophrenia was found in 19.6%, 18.7% and 14.2% respectively. Status of Consultation-Liaison Psychiatry needs to be improved by concerned physicians to deliver a better service to the patients in this hospital. DOI: http://dx.doi.org/10.3329/bmjk.v46i1-2.18235 Bang Med J (Khulna) 2013; 46 : 21-23